A High‐Lift Micro‐Aerial‐Robot Powered by Low‐Voltage and Long‐Endurance Dielectric Elastomer Actuators (Adv. Mater. 7/2022). Issue 7 (17th February 2022) - Ren, Zhijian; Kim, Suhan; Ji, Xiang; Zhu, Weikun; Niroui, Farnaz; Kong, Jing; Chen, Yufeng
Abstract : Soft Robots The muscle‐like dielectric elastomer actuators developed by Yufeng Chen and co‐workers in article number 2106757 lead to insect‐scale flapping‐wing aerial soft robots that resemble the size, weight, and performance of honeybees in nature. The actuators consist of soft elastomers and carbon nanotube electrodes, and they are made through novel fabrication methods to significantly reduce operating voltage and improve lifetime. Cover image credit: Photography and art by Julian Kamzol and Sampson Wilcox.